1998
DOI: 10.1093/jn/128.10.1661
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Inhibits Radiation-Induced Pneumonitis in Rats

Abstract: Radiation-induced lung injury frequently limits the total dose of thoracic radiotherapy that can be delivered, and the determinants of host susceptibility are poorly understood. To test the hypothesis that vitamin A status may be an important, modifiable host determinant of radiation-induced lung injury, we determined the effect of altered vitamin A status on radiation-induced lung inflammation in rats. WAG-Rij Y rats were fed a diet deficient in or supplemented with vitamin A (0 units/kg or 80,000 units/kg di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 21 publications
4
24
0
Order By: Relevance
“…Acute inflammation causes a reduction in serum vitamin A, ascribed to a reduction in the hepatic synthesis of retinol binding protein, and reduction in secretion of the retinol -retinol binding protein complex [6,9,10]. Conversely, animal studies have shown a protective effect of both retinol (vitamin A) and hcarotene supplementation against the inflammatory response [11,12]. Vitamin A deficiency causes night blindness and xerophthalmia, and is the leading cause of childhood blindness in developing countries [13].…”
Section: Introductionmentioning
confidence: 99%
“…Acute inflammation causes a reduction in serum vitamin A, ascribed to a reduction in the hepatic synthesis of retinol binding protein, and reduction in secretion of the retinol -retinol binding protein complex [6,9,10]. Conversely, animal studies have shown a protective effect of both retinol (vitamin A) and hcarotene supplementation against the inflammatory response [11,12]. Vitamin A deficiency causes night blindness and xerophthalmia, and is the leading cause of childhood blindness in developing countries [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among its many effects are the ability to regulate hematopoiesis, stimulate the production of acute phase proteins, induce the tissue inhibitor of metalloproteinase-1, regulate bone metabolism, and alter epithelial proliferation (2, 6 -10). Studies from our laboratories and others have also demonstrated that IL-11 can induce tissue fibrosis, regulate tissue myocyte and myofibroblast accumulation, alter airway physiology, and confer protection in the context of mucosal injury of the respiratory and gastrointestinal tracts (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…[15] In the present study, lutein has been evaluated as a radioprotector against gamma radiation-induced biochemical changes although lutein has been shown to be a moderate antioxidant in vitro in the previous studies. [16]…”
Section: Discussionmentioning
confidence: 99%